Camera obscura, camera lucida essays in honor of Annette Michelson - Allen, Richard 1959-; Turvey, Malcolm 1969- (Film culture in transition, 2003)
Annette Michelson's contributions to art and film criticism over the last three decades have been unparalleled. This volume honors her unique legacy with original essays by some of the many scholars who have been influenced by her work. Some continue her efforts to develop theoretical frameworks for understanding modernist art, while others practice her form of interdisciplinary criticism in relation to avant-garde and modernist art works and artists. Still others investigate and evaluate Michelson's work itself. All in some way pay homage to her extraordinary contribution